Implementation SHA512 Hash Function And Boyer-Moore String Matching Algorithm For Jpeg/exif Message Digest Compilation - Rachmad Fitriyanto; Anton Yudhana; Sunardi Sunardi (JOIN (Jurnal Online Informatika), 2019)
Security information method for JPEG/exif documents generally aims to prevent security attacks by protecting documents with password and watermark. Both methods cannot be used to determine the condition of data integrity at the detection stage of the information security cycle. Message Digest is the essence of a file that has a function as a digital fingerprint to represent data integrity. This study aims to compile digital fingerprints to detect changes that occurred in JPEG / exif documents in information security. The research phase consists of five stages. The first stage, identification of the JPEG / exif document structure conducted using the Boyer-Moore string matching algorithm to find JPEG/exif segments location. The Second stage is segment content acquisition, conducted based on segment location and length obtained. The Third step, computing message digest for each segment using SHA512 hash function. Fourth stage, JPEG / exif document modification experiments to identified affected segments. The fifth stage is selecting and combining the hash value of the segment into the message digest. The obtained result shows the message digest for JPEG/exif documents composed of three hash values. The SOI segment hash value used to detect modifications for JPEG to png conversion and image editing. The APP1 hash value used to detect metadata editing. The SOF0 hash values use to detect modification for image recoloring, cropping and resizing — the combination from three hash values as JPEG/exif’s message digest.